Tafakkur on Malik Badri’s View - Khusnul Khotimah; Shofiyyah Hanim; Ussisa ‘alat Taqwa (University of Darussalam Gontor, Indonesia, 2023)
Tafakkur is a practice of deep contemplation and reflection, holds a significant place within Islamic spirituality as a means of attaining profound insights and a deeper connection with the Divine. This journal article delves on tafakkur into the perspective of renowned scholar Malik Badri employing a qualitative research approach to gain a comprehensive understanding of his views. Through an in-depth analysis method of Malik Badri's writings, this research explores his interpretations of tafakkur as a spiritual and intellectual endeavor. Thus, the researcher uncover the nuances of Badri's insights and their implications for personal growth, worship, and the relationship with Allah. Badri's perspective sheds light on how tafakkur serves as a transformative tool for believers, offering a pathway to enrich their spiritual journey and foster a deeper appreciation of the Creator's wisdom. Furthermore, this research highlights the historical and cultural context that shaped Malik Badri's thoughts on tafakkur, tracing the lineage of this concept within Islamic thought. By engaging with Badri's writings, speeches, and interviews, we decipher his unique approach to tafakkur and its alignment with traditional Islamic teachings. In essence, this research contributes to the existing body of knowledge by presenting a qualitative exploration of Malik Badri's viewpoint on tafakkur. The insights gained from this research offer valuable guidance for individuals seeking to engage in meaningful contemplation, fostering a more profound connection with spirituality and a deeper understanding of Islamic principles.